The effect of specific exercises on improving motor response and attention focus for performing the motor sequence on the balance beam - الحمزة, م. م. امال عبد; كاظم, ا. م. د سعاد خيري; Al-Karawi, Prof. Dr. Salam Mohammed Hamza (Sulaimani Journal for Humanities, 2026)
This research aims to identify the focus of attention and motor response among female students in artistic gymnastics during the 2024-2025 academic year. - Developing and implementing specific exercises with the students. - Determining the effect of these exercises on improving focus of attention and motor response in performing the movement sequence on the balance beam. - The research hypothesis is that there is a statistically significant effect of these specific exercises on focus of attention and motor response in performing the movement sequence on the balance beam for female students. The researchers used the experimental method, and their study population consisted of (18) third-year female students from the College of Physical Education at the University of Babylon. The researchers used a device (attention focus and motor response speed) designed to measure mental abilities (response speed and attention focus) and manufactured according to electronic and electrical manufacturing procedures. This device measures mental processes using electronic circuits. The results showed that the specific exercises had an effect on the students' focus of attention, improved their performance level and motor response speed, and improved their performance level in the movement sequence on the balance beam. The students responded well to the cognitive abilities measurement device (attention and response speed). The researchers recommended applying the exercises to another group and emphasized the importance of utilizing and implementing these specific exercises.